The Mafeje and the UCT saga: unfinished business? - Ntsebeza, Lungisile (Social dynamics, 2014)
This article focuses on the thorny and vexed relationship between Archie Mafeje, a black South African scholar and the University of Cape Town. Mafeje was appointed on merit in 1968 as Senior Lecturer in Social Anthropology at the University of Cape Town. His appointment was rescinded by the University Council acting under pressure from the apartheid state. With the imminent demise of apartheid, Mafeje re-applied in the early 1990s for a position at the University of Cape Town in the early 1990s. His application was turned down. This piece offers a detailed reading and analysis of what became known as the "Mafeje affair" and raises issues about the meaning of transformation at the University of Cape Town.